Costs of Change, Political Polarization, and Re-election Hurdles - Hans Gersbach; Philippe Muller; Oriol Tejada (ETH Zurich, CER-ETH - Center of Economic Research, 2015)
We develop and study a two-period model of political competition with office- and policymotivated candidates, in which (i) changes of policies impose costs on all individuals and (ii) such costs increase with the magnitude of the policy change. We show that there is an optimal positive level of costs of change that minimizes policy polarization and maximizes welfare. One interpretation of this finding is that societies with intermediate levels of conservatism achieve the highest welfare and the lowest polarization levels. We apply our model to the design of optimal re-election hurdles. In particular, we show that raising the vote-share needed for re-election above 50% weakly reduces policy polarization and tends to increase welfare. Furthermore, we identify circumstances where the optimal re-election hurdle is strictly larger than 50%.
Keywords: D7; H4; 330; elections; democracy; political polarization; costs of change; re-election hurdles; political contracts